Square root(3x - 2) = 4 - x
Square both side
3x-2 =(4-x)^2
3x - 2 =16 -8x +x^2
0= x^2 -11x +18
0r x^2 -11x +18=0
x^2 -9x -2x+18=0
x(x - 9) -2(x - 9)=0
(x - 2) (x - 9) =0
Therefore x =2 and x=9
But x=9 does not satisfy the equation therefore x=2 is the only answer
2006-09-15 03:22:55
·
answer #1
·
answered by Amar Soni 7
·
0⤊
0⤋
square root(3x - 2) = 4 - x
Taking square on both sides we get,
3x -2 = (4 - x) ^2
3x -2 = 16 - 8x - x^2
x^2 - 8x -3x + 16 +2 = 0
x^2 - 11x +18 =0
( x - 9) (x - 2) = 0
x-9 =0 or x-2 =0
x=9 or x=2
The Solution is 2 as it satisfy the given equation.
2006-09-15 10:35:33
·
answer #2
·
answered by king2006 2
·
0⤊
0⤋
It's a polynomial equation. therefore in this case a quadratic. so let see:
you can get of the square root by squaring both sides.
you can expand (4-x)^2 to (4^2 - 2*4*x+x^2).
then add and substract
and you will come up with something like this
x^2-11x+18=0
factorizing; (x-2)(x-9)
so values for x are:
x1=2
x2=9
2006-09-15 10:20:25
·
answer #3
·
answered by papiloghost 3
·
0⤊
0⤋
take square of both sides
(3x-2) = (4-x)^2 = 16-8x+x^2
take 3x-2 to the right
0 = 18-11x+x^2
= 18-9x-2x+x^2
= 9(2-x)-x(2-x)
=(9-x) (2-x)
so x = 2 or 9
but x =9 makes the rhs -ve so x=2 is the solution
Note
x^2 = 16 means x= 4 or -4
but sqrt(16) is defined to be positive sqrt so 4
2006-09-15 10:43:25
·
answer #4
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
when u take the square root over:
3x - 2 = (4 -x )squared
3x - 2 = (4-x)(4-x)
3x - 2 = 16 -4x -4x -xsquared
3x -2- 16 + 4x +4x + xsquared = 0
xsquared + 11x -18 = 0
then u use the quadratic formula>>>
x= b +/- square root (bsquared - 4ac) over 2ac
where b = 11, c = -18, a =1
x = 1.4462 or -12.446
is it close enough? :p
2006-09-15 10:07:25
·
answer #5
·
answered by ChEkNa . 4
·
0⤊
1⤋
square root(3x-2) = 4-x
3x-2 = (4-x)(4-x)
3x-2 = 16-8x+x^2
-18 = x^2-8x
x^2-11x+18 = 0
x^2-11x+18 = (x - 2)(x - 9)
Therefore, x = 2 or 9(reject)
Thus, the answer is x = 2.
2006-09-15 10:29:28
·
answer #6
·
answered by b0b0link 2
·
0⤊
0⤋
The answer is not just 2, I believe it's also 9. Square both sides, then re-arrange to be in the form of a classic quadratic equation. Then you'll be able to factor, just like your teachers told you. There is enough information here for you to proceed and do the work yourself. Good luck.
2006-09-15 10:11:21
·
answer #7
·
answered by curious1223 3
·
0⤊
0⤋
[Square root(3x-2)]Squared=(4-x)squared
3x-2=x Squared - 8x +16
0=x squared -11x +18
0= (x-9)(x-2)
therefore: x=9 & x=2
AND: x=2 is the acceptable value
2006-09-15 10:09:05
·
answer #8
·
answered by pitsomos 2
·
0⤊
0⤋
1st .. square both sides .....
3x - 2 = 16 - 8x + x^2
standard form ... 3x -2 = x^2 - 8x +16
set-up quadratic .... x^2 -11x+18 = 0
factor (x-9) (x-2) = 0 x=(2,9)
check sq rt(3(9)-2) = 4 - 9
sq rt (27-2) = -5
sq rt (25) = plus & minus 5 (check) (-5) (-5) = 25
sqrt (3(2) - 2) = 4 - 2
sqrt (6-2) = 2
sqrt (4) = 2 check
answers are 2 & 9
2006-09-15 10:10:05
·
answer #9
·
answered by Brian D 5
·
0⤊
0⤋
sqrt(3x - 2) = 4 - x
square both sides
3x - 2 = (4 - x)^2
3x - 2 = (4 - x)(4 - x)
3x - 2 = 16 - 4x - 4x + x^2
3x - 2 = 16 - 8x + x^2
x^2 - 11x + 18 = 0
(x - 9)(x - 2) = 0
x = 2 or 9
2006-09-15 20:28:19
·
answer #10
·
answered by Sherman81 6
·
0⤊
0⤋